The Relationship Between Digital Marketing, Brand Ambassador, and Product Mixes to Skintific Brand Cosmetic Loyalty to Young Women in Pontianak City - Arnelita Yolanda; Dewi Santika (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study investigates the influence of digital marketing, brand ambassador, and product mixes on the brand loyalty of Skintific cosmetic products among young women in Pontianak, Indonesia. Employing a quantitative causal approach, data were collected via questionnaires from 166 respondents, selected through a quota sampling method across Pontianak's municipalities. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results demonstrate that all three variables—digital marketing, brand ambassador, and product mixes—have a significant positive effect on brand loyalty. Notably, the product mixes emerged as the most influential factor, underscoring the paramount importance of product diversity, quality, and availability in fostering consumer loyalty. Brand ambassador was the second most significant factor, followed by digital marketing. This research provides valuable insights for cosmetic brands, suggesting that while digital and ambassador strategies are effective, the fundamental driver of loyalty lies in a superior product portfolio. The study offers a validated model for understanding brand loyalty dynamics in the competitive Indonesian beauty market.